Предмет: Алгебра,
автор: lluHgBuH1
Помогите решить пожалуйста!!!
Приложения:
Ответы
Автор ответа:
0
1) (a²+b²-c²)-(b²+c²-a²)+(c²-a²) = a²-c²
a²+b²-c²-b²-c²+a²+c²-a² = a²-c²
2a²-2c²+c²-a² = a²-c²
-c²+a² = a²-c²
a²-c² = a²-c² (И)
2) (4-3a²)-a²+(7+2a²)-(-2a²+11) = 0
4-3a²-a²+7+2a²+2a²-11 = 0
-4a²+11+4a²-11 = 0
0 = 0 (И)
3) (x³+4x²)-(x+6)+(1+x-x³) = 4x²-5
x³+4x²-x-6+1+x-x³ = 4x²-5
4x²-6+1 = 4x²-5
4x²-5 = 4x²-5 (И)
a²+b²-c²-b²-c²+a²+c²-a² = a²-c²
2a²-2c²+c²-a² = a²-c²
-c²+a² = a²-c²
a²-c² = a²-c² (И)
2) (4-3a²)-a²+(7+2a²)-(-2a²+11) = 0
4-3a²-a²+7+2a²+2a²-11 = 0
-4a²+11+4a²-11 = 0
0 = 0 (И)
3) (x³+4x²)-(x+6)+(1+x-x³) = 4x²-5
x³+4x²-x-6+1+x-x³ = 4x²-5
4x²-6+1 = 4x²-5
4x²-5 = 4x²-5 (И)
Автор ответа:
0
(И) - "истинно"
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Алгебра,
автор: discordlodka47
Предмет: История,
автор: dmytrolishchyna
Предмет: Химия,
автор: tosia45
Предмет: Математика,
автор: shuragasparyan